Enhanced Magnetic Properties of Nd15Fe77B8 Alloy Powders Produced by Melt-Spinning Technique - Ozturk, Sultan; Icin, Kursat; Ozturk, Bulent; Topal, Ugur; Odabasi, Hulya Kaftelen; Gobuluk, Metin; Cora, Omer Necati (Springer, 2017)
Rapidly solidified Nd15Fe77B8 alloy powders were produced by means of melt-spinning method in high-vacuum atmosphere to achieve improved magnetic and thermal properties. To this goal, a vacuum milling apparatus was designed and constructed to ball-mill the melt-spun powders in a surfactant active atmosphere. Various milling times were experimented to reveal the effect of the milling time on the mean particle size and other size-dependent properties such as magnetism and Curie temperature. Grain structure, cooling rate, and phase structure of the produced powders were also investigated. The Curie points shifted to higher temperatures from the ingot condition to surfactant active ball-milling and the values for Nd15Fe77B8 ingot alloy, melt-spun powders, and surfactant active ball-milled powders were 552 K, 595 K, and 604 K (279 A degrees C, 322 A degrees C, and 331 A degrees C), respectively. It was noted that the surfactant active ball-milling process improved the magnetic and thermal properties of melt-spun Nd15Fe77B8 alloy powders. Compared to relevant literature, the coercivity of powders increased significantly with increasing milling time and decreasing in powder size. The coercivity value as high as 3427 kA m(-1) was obtained.
Keywords: Ndfeb Magnets; Single-Crystal; Fe; Surfactant; Behavior; Microstructure; Nanoparticles; Coercivity; Submicron; Droplets